High-resolution ultrasound of peripheral neuropathies in rheumatological patients: An overview of clinical applications and imaging findings - Zaottini, Federico; Picasso, Riccardo; Pistoia, Federico; Sanguinetti, Sara; Pansecchi, Michelle; Tovt, Luca; Viglino, Umberto; Cabona, Corrado; Garnero, Martina; Benedetti, Luana; Martinoli, Carlo (Frontiers in Medicine, 2022)
Peripheral neuropathies are surprisingly common and can be associated with a wide range of conditions, including rheumatological diseases. Although the association of the two disorders can be coincidental, an underlying pathogenic link can occur in many instances, which can affect treatment options. The presentation of a peripheral neuropathy can be multifaceted, an important consideration when recognizing the condition and optimizing its diagnosis. Furthermore, adopting the state-of-art diagnostic strategies will help physicians when treating patients with rheumatic diseases who go on to develop a peripheral neuropathy. In particular, a diagnosis based only on the clinical history and on nerve conduction studies possibly may not reveal subtle malfunctions in the early stages of the disease or, indeed, expose abnormalities in structures surrounding the nerves and muscles, thus limiting the possibility of a timely diagnosis. High Resolution Ultrasound (HRSU) is an increasingly-adopted tool used to support the diagnosis and follow-up of both joint disorders in rheumatology and peripheral neuropathies of different aetiologies. In this Review, the HRUS role in the diagnosis of patients with peripheral neuropathy in the context of rheumatic diseases is discussed, describing the different pathological findings and the patterns of nerve involvement in the most common syndromes of rheumatological interest.